A selective and stable Fe/TiO2 catalyst for selective hydrogenation of butadiene in alkene-rich stream. Issue 57 (24th June 2021) - Wang, Zhao; Santander de Soto, Laura; Méthivier, Christophe; Casale, Sandra; Louis, Catherine; Delannoy, Laurent
Abstract : The Fe/TiO2 catalyst shows high selectivity to alkenes at high butadiene conversion and good stability at 175 °C. Abstract : The replacement of precious metals by more abundant and therefore much less expensive metals remains a very important challenge in catalysis. A Fe/TiO2 catalyst prepared by deposition–precipitation with urea showed very high selectivity to alkenes (>99%), even at high conversion (>90%), in selective hydrogenation of butadiene in an excess of propene. Its activity is very stable at 175 °C whereas the catalyst deactivates at 50 °C, although it is also initially very active. The presence of metallic iron seems to be necessary to ensure these excellent performances.